Learning-Centered Community College and English as a second language programme - Krishna Bista, (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2011)
This paper reviews the major features of learning-centered community colleges that offer educational programmes and experiences for learners, based on individual needs. By citing some exemplary learning colleges, the author examines the concepts and ideas of learning-centered colleges in teaching English as a Second Language (ESL) programmes. Emphasis is given to the environment, learning goals, performance and feedback, and rubrics as successful learning tools in teaching ESL in the colleges. ESL instructors are encouraged to transform the learning culture from that of teacher centered to student-centered environments.